(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Some structures of vanous Hymenoptera Chalcidoidea and their functions ( * ) The various actions by which a paras1t1c insect arrives at a choice of a suitable host bave been much discussed. The last review of the subject was that of VINSON (1976), who put forward a synthesis pointing out the connections between the operations of choosing a habitat and victim, and the means with which · these operations were carried out (fig. 1). Among Hymenoptera Chalcidoidea, which include the smallest and most specialized insects in existence, even very accurate morphological studies suffer from the many limitations imposed by the optical microscope. In consequence, ethological research on these insects provides us with only approximate information on the use of their apparatus. This present study wishes to draw attention to the importance of the S.E.M. (Scanning Electron Microscope) for really detailed investigation of the structures. The exploration of the cuticle with the electron beam presents to us, in fact, a complexity ·of appendices, of tegumental projections and of sensory apparatus considerably greater than that previously known. The modifications of the same structure in different species, in relation to the tasks for which it is used, often reveal extraordinary adaptations. Examination of some species of Chalcidoidea, even if only superficial and to gain a general impression, gives us a much more adequate idea of the structural reality of the organs and appendices of the insect. In this way the richness and range of means available to these insects clarifies their relations with their surroundings and their capacity to receive information and react to it. Some photographs taken by the S.E.M. illustrate the subject clearly, removing the sense of the unknown that surrounded the behaviour of these insects